Review of Alexandros Nafpliotis's Britain and the Greek Colonels: Accommodating the Junta in the Cold War - Skalidakis, Yannis (Historein, 2014)
Review of Alexandros Nafpliotis, Britain and the Greek Colonels: Accommodating the Junta in the Cold War. London: IB Tauris, 2013. 307 pp.